Using Learner-Centered, Simulation-Based Training to Improve Medical Students' Procedural Skills. (13th March 2017) - Toy, Serkan; McKay, Robert SF; Walker, James L; Johnson, Scott; Arnett, Jacob L
Purpose: To evaluate the effectiveness of a learner-centered, simulation-based training developed to help medical students improve their procedural skills in intubation, arterial line placement, lumbar puncture, and central line insertion. Method: The study participants were second and third year medical students. Anesthesiology residents provided the training and evaluated students' procedural skills. Two residents were present at each station to train the medical students who rotated through all 4 stations. Pre/posttraining assessment of confidence, knowledge, and procedural skills was done using a survey, a multiple-choice test, and procedural checklists, respectively. Results: In total, 24 students were trained in six 4-hour sessions. Students reported feeling significantly more confident, after training, in performing all 4 procedures on a real patient ( P < .001). Paired-samples t tests indicated statistically significant improvement in knowledge scores for intubation, t (23) = −2.92, P < .001, and arterial line placement, t (23) = −2.75, P < .001. Procedural performance scores for intubation ( t (23) = −17.29, P < .001), arterial line placement ( t (23) = −19.75, P < .001), lumbar puncture ( t (23) = −16.27, P < .001), and central line placement ( t (23) = −17.25, P < .001) showed significant improvement. Intraclass correlation coefficients indicated high reliability in checklist scores for all procedures. Conclusions: The simulation sessions allowed each medical student to receive individual attention from 2 residents for each procedure. Students' written comments indicated that this training modality was well received. Results showed that medical students improved their self-confidence, knowledge, and skills in the aforementioned procedures.